Penerapan Model Pembelajaran Creative Problem Solving (CPS) untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika di Sekolah Dasar - Angelina, Rara; Zainil, Melva; Indrawati, Tin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this study was to describe the application of Creative Problem Solving (CPS) learning models to improve mathematical problem solving skills in class IV SDN 13 Simpang Haru, Padang City. This type of research is classroom action research, with a qualitative and quantitative approach. The subject of this study was the fourth grade students and teachers of SDN 13 Simpang Haru. The results of the research on each cycle showed an increase. RPP cycle I 85.7% (B), cycle II 92.86% (SB). Implementation of the teacher aspect cycle I 77.05% (B), cycle II 95.8% (SB). The implementation of the student aspect in the first cycle is 77.05% (B), the second cycle is 95.8% (SB). Improvement of Mathematical Problem Solving cycle I 74.3 (C), Cycle II 86 (SB) It can be concluded that the Creatie Problem Solving (CPS) model can improve mathematical problem solving. Keywords: CPS model, learning outcomes